Meningkatkan Efektivitas Layanan Administrasi Pendidikan Melalui Profesionalisme Tata Usaha Di MTs Hubbbul Wathon - Iswanto; Uswatun Umi Zarhasih; Cici Nuryathrib; Amelia Putri (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
Education is one of the important pillars in building a developed and prosperous nation. This research uses a qualitative method and interview and observation techniques. The formulation of the problem is how the role of professional administrative staff in improving the quality of education administration services at Mts Hubbul Wathon? What are the obstacles and solutions for professional administrative staff in improving the quality of education administration services at Mts Hubbul Wathon? The Administration is an important part of an educational institution, playing a role in managing administration and supporting teaching and learning activities. In this study, Syarif as the Administration at Mts Hubbul Wathon said that professional Administration has several important roles. First, compiling and managing administrative documents. Second, smoothening the teaching and learning process. TU ensures the availability of facilities and infrastructure. Third, managing school finances. The obstacles of an administrator are: First, the lack of competent and trained administrative staff in managing education administration. Second, the limited workspace and office equipment. Third, lack of coordination and communication. Fourth, lack of motivation and work spirit. Then the solution is: First, recruiting competent administrative staff who have the appropriate qualifications. Second, equipping the workspace with modern and ergonomic office equipment to support work comfort and productivity. Third, improving coordination and communication with other parties. And finally, how to increase motivation and work spirit.